The C-Band All-Sky Survey (C-BASS): template fitting of diffuse galactic microwave emission in the northern sky. Issue 4 (5th May 2022) - Harper, S E; Dickinson, C; Barr, A; Cepeda-Arroita, R; Grumitt, R D P; Heilgendorff, H M; Jew, L; Jonas, J L; Jones, M E; Leahy, J P; Leech, J; Pearson, T J; et al.
ABSTRACT: The C-Band All-Sky Survey (C-BASS) has observed the Galaxy at 4.76 GHz with an angular resolution of 0${_{.}^{°}}$ 73 full-width half-maximum, and detected Galactic synchrotron emission with high signal-to-noise ratio over the entire northern sky (δ > −15 ○ ). We present the results of a spatial correlation analysis of Galactic foregrounds at mid-to-high ( b > 10 ○ ) Galactic latitudes using a preliminary version of the C-BASS intensity map. We jointly fit for synchrotron, dust, and free–free components between 20 and 1000 GHz and look for differences in the Galactic synchrotron spectrum, and the emissivity of anomalous microwave emission (AME) when using either the C-BASS map or the 408-MHz all-sky map to trace synchrotron emission. We find marginal evidence for a steepening (<Δ β > = −0.06 ± 0.02) of the Galactic synchrotron spectrum at high frequencies resulting in a mean spectral index of < β > = −3.10 ± 0.02 over 4.76–22.8 GHz. Further, we find that the synchrotron emission can be well modelled by a single power law up to a few tens of GHz. Due to this, we find that the AME emissivity is not sensitive to changing the synchrotron tracer from the 408-MHz map to the 4.76-GHz map. We interpret this as strong evidence for the origin of AME being spinning dust emission.